Histone deacetylase inhibitors suppress IFNalpha-induced up-regulation of promyelocytic leukemia protein - Vlasáková, Jana; Nováková, Zora; Rossmeislová, Lenka; Kahle, Michal; Hozák, Pavel; Hodny, Zdenek (Blood, 2007)
Promyelocytic leukemia nuclear bodies (PML NBs), the structural domains of the eukaryotic cell nucleus, play a role in cancer and apoptosis, and their involvement in antiviral mechanisms mediated by interferons (IFNs) is proposed. IFNs dramatically increase the transcription of the PML gene. In this study, we have shown that the response of 2 structural PML NB components, PML and Sp100, to interferon-alpha (IFNalpha) was suppressed in cells simultaneously treated with histone deacetylase (HDAC) inhibitors (trichostatin A, sodium butyrate, MS-275, SAHA, and valproic acid). Trichostatin A (TSA) blocked the increase of PML NB number and suppressed up-regulation of PML mRNA and protein levels in several human cell lines and in normal diploid skin fibroblasts. Moreover, IFNalpha induction of IRF-1 was also inhibited by TSA, although incompletely. Analysis of cellular fractions did not show any defects in cytoplasmic-nuclear transport of STAT2, a component of transcription factor ISGF3 responsible for IFNalpha/beta-dependent gene transcription. Moreover, chromatin immunoprecipitation showed that after IFNalpha stimulation STAT2 binds to ISRE element of PML promoter even in the presence of TSA and thus excluded STAT2-dependent mechanism of TSA effect. These results indicate that the action of histone deacetylases is necessary for the full transcriptional activation of IFNalpha-stimulated genes.
Keywords: Tumor Cells, Cultured; Up-Regulation; Cells, Cultured; Promyelocytic Leukemia Protein; Transcription Factors; Humans; Neoplasm Proteins; Tumor Suppressor Proteins; transkripční faktory; nádorové supresorové proteiny; Histone Deacetylase Inhibitors; RNA, Neoplasm; aktivace transkripce; Nuclear Proteins; jaderné proteiny; RNA nádorová; inhibitory histondeacetylas; inhibitory enzymů; nádorové buňky kultivované; Transcriptional Activation; nádorové proteiny; kultivované buňky; upregulace; STAT2 Transcription Factor; interferon alfa; lidé; transkripční faktor STAT2; Interferon-alpha; Enzyme Inhibitors; protein promyelocytické leukemie